DEVELOPMENT OF PHYSICS E-LEARNING BASED ON PROBLEM BASED LEARNING TO IMPROVE STUDENTS' HIGH-LEVEL THINKING ABILITIES AND LEARNING INTERESTS IN FLUID MATERIALS - Yoli Wilanda Fitri; Fakhruddin Fakhruddin; M Rahmad (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
One of method increase ability think level tall that is with application of suitable learning media For competence 21st century one of them is e-learning. E-learning in research This developed with the PBL learning model which consists of above five syntax with objective capable increase HOTS skills and interests Study students . Based on results analysis needs carried out by researchers obtained that 91.5% of students interested For learning with using e-learning. Research This aiming For describe development e-learning physics based on problem based learning , acquiring e-learning physics that is feasible and practical For used in learning physics . Physics e-learning validated by 3 validators using sheet evaluation validity , as well as tested practicality by 3 teachers and 20 participants educate use sheet evaluation practicality . Research results show that e-learning physics based on problem based learning declared very worthy by the validator with mark validation 3.49 for material , 3.51 for media and 3.52 for pedagogy . Besides That based on practicality test results obtained the average value of teacher practicality is 88.00 (very practical) and the average practicality is 88.00 (very practical). student 89.50 (very practical).